PARTISIPASI MASYARAKAT DALAM PROGRAM TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN MENURUT PERSPEKTIF ISO 26000 - Agustin Teras Narang; Daniel Pradina Oktavian (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
The implementation of the social and environmental responsibility program (TJSL) has been mandated through Law Number 40 of 2007 concerning Limited Liability Companies (UUPT). Article 74 paragraph (1) UUPT. The implementation of the CSR program is a manifestation of efforts to build good reciprocal relationships with all stakeholders, both the government and all elements of society. Often, in the implementation of the CSR program, the benefits received by the community are not appropriate or do not have a maximum impact on the community and the environment. This study aims to determine the concept of community participation contained in the CSR or CSR guidelines in accordance with ISO 26000. The research methods used in this study are normative legal research methods and descriptive qualitative research methods. This method is used to study, maintain, and develop positive legal structures with logic buildings with a written guideline approach. Community participation in the implementation of Social and Environmental Responsibility (TJSL) is absolutely necessary to be given proper space. Community participation not only allows the community to receive program benefits, but is also active in all processes or stages in the implementation of CSR. ISO 26000 emphasizes the importance of community participation in Social Responsibility (SR) in the main issues of community development. Community involvement and development is an integral part of the concept of sustainable development.